Respuesta :

Answer: k = -1 +/- √769

Step-by-step explanation:

48x - ky = 11

-48x           -48x

         -ky = -48x + 11

         [tex]\frac{-ky}{-k} = \frac{-48x}{-k} + \frac{11}{-k}[/tex]    

           [tex]y =\frac{48x}{k} - \frac{11}{k}[/tex]

Slope: [tex]\frac{48}{k}[/tex]

*************************************************************************

 (k + 2)x + 16y = -19

- (k + 2)x             -(k + 2)x

                 16y = -(k + 2)x - 19

                  [tex]\frac{16y}{16} = -\frac{(k + 2)x}{16} - \frac{19}{16}[/tex]

                  [tex]y = -\frac{(k + 2)x}{16} - \frac{19}{16}[/tex]

Slope: [tex]-\frac{(k + 2)}{16}[/tex]

**********************************************************************************

[tex]\frac{48}{k}[/tex] and [tex]-\frac{(k + 2)}{16}[/tex] are perpendicular so they have opposite signs and are reciprocals of each other.  When multiplied by its reciprocal, their product equals -1.

[tex]-\frac{(k + 2)}{16}[/tex] *  [tex]\frac{k}{48}[/tex] = -1

[tex]\frac{(k + 2)k}{16(48)}[/tex] = 1

Cross multiply, then solve for the variable.

(k + 2)(k) = 16(48)

k² + 2k - 768 = 0

Use quadratic formula to solve:

k = -1 +/- √769